AB0613 Clinical and Laboratory Differences between SSC Patients with and without Diastolic Dysfunction. (10th June 2014) - Jurisic, Z.; Marasović Krstulović, D.; Perkovic, D.; Boric, K.; Radic, M.; Martinovic Kaliterna, D.
Abstract : Background: Left ventricular diastolic dysfunction (LVDD) is the most common cardiac abnormality in systemic sclerosis (SSc). It is known that aging is a primary determinant of LVDD in SSc patients and many of the clinical factors associated with LVDD were no longer associated after simply adjusting for age. Objectives: The aim of this study was to determine clinical and laboratory parameters of SSc patients with and without LVDD matched for age. Methods: We studied 13 SSc patients with preserved left ventricular ejection fraction (LVEF) and LVDD, and 13 SSc patients without LVDD matched for age, sex, body mass index and smoking status. LVDD was defined and classified according to the American Society of Echocardiography recommendations. Serum IL-6 and NT-proBNP levels were measured and subjects were evaluated by conventional and pulsed-wave tissue Doppler echocardiography and by the six minute walk test (6MWT). Results: There was no difference between SSc patients with and without LVDD according to heart rate, systolic and diastolic blood pressure, left ventricular mass index, prevalence of pulmonary artery hypertension, and antibody status. SSc patients with LVDD had longer duration of SSc than SSc patients without LVDD (16.0 vs 6.65 yrs; P =0.004), and had higher EUSTAR score (5.77 vs 3.12; P =0.001). The serum level of IL-6 (6.39 vs 2.94 pg/ml; P =0.021) and NT-proBNP (24.78 vs 10.12 pmol/L; P=0.003) were significantly increased in SSc patients with LVDD. The 6MWT distance was shorter in SSc patients with LVDD as compared to those without LVDD (326.46 vs 398.69 m; P =0.034). Also, desaturation during the 6MWT was more significant in SSc patients with LVDD (-3.38% vs -1.92%; P =0.022). Conclusions: SSc patients with LVDD had longer disease duration and higher disease activity (EUSTAR) scores. SSc patients with LVDD showed significantly increased serum IL-6 and NT-proBNP levels in comparison with those without LVDD. LVDD is associated with decreased exercise capacity in SSc patients. References: Hinchcliff M, Desai CS, Varga J, Shah SJ. Prevalence, prognosis, and factors associated with left ventricular diastolic dysfunction in systemic sclerosis. Clin Exp Rheumatol. 2012;30:30-7. Scala E, Pallotta S, Frezzolini A et al. Cytokine and chemokine levels in systemic sclerosis: relationship with cutaneous and internal organ involvement. Clin Exp Immunol 2004;138:540-6. Nagueh SF, Appleton CP, Gillebert TC et al. Recommendations for the evaluation of left ventricular diastolic function by echocardiography. J Am Soc Echocardiogr 2009;22:107-33. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5652